Analisa Kegiatan dan Layanan PT. Kereta Api Cepat Indonesia China : Penerapan Service Blueprint, Kualitas Layanan, Pertemuan Layanan dan Servicescape - Lia Siti Julaeha; Prajarto Budi Wibowo; Muhammad Ibnu Darmawan; Rosyid Nuryadin (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
PT Kereta Api Cepat Indonesia China (KCIC) is the pioneer of high-speed rail services in Indonesia under the Whoosh brand, connecting Jakarta and Bandung. Despite offering a modern mobility solution, its occupancy rate remains suboptimal, with passenger load factor reaching only 63.35% in October 2024. This study aims to analyze KCIC’s service operations through the service blueprint approach, focusing on service quality, service encounter, and servicescape. A qualitative descriptive research method was applied, with data collected through direct observations, interviews with KCIC managers and passengers, and document analysis. The findings indicate that while Whoosh offers technologically advanced services with a modern servicescape, issues persist in customer interactions, reservation system efficiency, and service responsiveness. The service blueprint analysis suggests that enhancing customer touchpoints, optimizing digital ticketing technology, and training staff in service encounter can improve customer experience. The study's implications provide strategic recommendations for KCIC to enhance its competitiveness through more efficient service management and customer-oriented improvements.